EKSISTENSI CSR SEBAGAI AGEN PEMBANGUNAN DI PROVINSI RIAU - Herman; Rosmita (SISI LAIN REALITA, 2019)
Development is a process of change made by the government to the community. In this paper the development is carried out through CSR activities in Riau Province through the elements of stakeholders consisting of the Company itself, the community as a platform for CSR activities, and the Government as the regulatory and supervisory function. This paper discusses how CSR as an agent for poverty alleviation can be done through community empowerment activities which include development, improving the quality of human resources, education, health, economy and even the environment. The role of stakeholders in this case is the benefits received by the company in implementing CSR activities, the benefits of implementing CSR for the community, and the benefits of implementing CSR for the government. While the CSR controversy can be seen through the aspect of regulation that focuses on sanctions against companies that do not implement CSR and the amount of costs that must be incurred by the company in its implementation. The oversight function in this case is the Regional Regulation in Riau Province where the supervision has not been going well. Whereas the determination of Ring consisting of Ring 1, Ring 2 and Ring 3 also has not proceeded in accordance with what should have been where many villages were supposed to get the Ring 1 category but were not categorized. So this thing needs an action so that in the future it can run as it should.